Constrained optimization analysis and design of laterally loaded piles - Rahul Koshal Dubey (2009)
Finding an accurate solution to a laterally loaded pile problem is often of intense debate among academics specializing in the field of Civil Engineering. Several methodologies have been applied such as p-y curves and the elastic continuum method. This project examines the solving of laterally loaded piles by first using deterministic analysis. Some case studies will be discussed in this project to illustrate the nature of laterally loaded piles. This method involves a computational spreadsheet procedure using non-linear p-y curves. There are mainly two aspects to this; an optimization application called Solver in Microsoft Excel, where constrained optimization analysis is carried out together with Visual Basic (VBA), a programming environment. The pile is modeled as beam on a non-linear springs subjected to lateral loads. User input of a relevant p-y model is carried out. This is important as the appropriate model used provides a better solution, which is often debated by engineers and academics. The method is used on case studies where the results are subsequently compared to those from other programs such as LPILE, a program from Ensoft. Probabilistic analysis using Microsoft Excel is also discussed where certain variables such as pile and soil properties are treated as random variables and spatial autocorrelation of soil properties are taken into consideration. The Hasofer-Lind reliability index is used where the user can define a specific limit state and a resulting probability of failure can be obtained. An obvious advantage of using Excel spreadsheet over other programs is that minimal programming is required. Furthermore, results provided by Excel are compatible with those obtained from other programs such as LPILE. Microsoft Excel, a readily available program has a tremendous potential of being very useful in the resolution of engineering problems such as laterally loaded piles.